2018
DOI: 10.1016/j.matbio.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Microfibril-associated glycoproteins MAGP-1 and MAGP-2 in disease

Abstract: Microfibril-associated glycoproteins 1 and 2 (MAGP-1, MAGP-2) are protein components of extracellular matrix microfibrils. These proteins interact with fibrillin, the core component of microfibrils, and impart unique biological properties that influence microfibril function in vertebrates. MAGPs bind active forms of TGFβ and BMPs and are capable of modulating Notch signaling. Mutations in MAGP-1 or MAGP-2 have been linked to thoracic aneurysms and metabolic disease in humans. MAGP-2 has also been shown to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 86 publications
(118 reference statements)
0
43
0
Order By: Relevance
“…Microfibrillar-associated proteins (MFAPs) are a group of extracellular matrix glycoproteins including five subfamily members (MFAP1~5), these proteins have been reported to play a role in microfibril assembly and tissue homeostasis. [10][11][12] Among these five members, Microfibrilassociated protein 2 (MFAP2, also known as MAGP-1), with its coding gene located at 1p36.13, was reported to be associated with different kinds of malignant cancers in recent years. Chen et al showed that MFAP2 was overexpressed in melanoma and promoted invasion and migration abilities of melanoma through regulating the EMT-related proteins and Wnt/beta-catenin pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Microfibrillar-associated proteins (MFAPs) are a group of extracellular matrix glycoproteins including five subfamily members (MFAP1~5), these proteins have been reported to play a role in microfibril assembly and tissue homeostasis. [10][11][12] Among these five members, Microfibrilassociated protein 2 (MFAP2, also known as MAGP-1), with its coding gene located at 1p36.13, was reported to be associated with different kinds of malignant cancers in recent years. Chen et al showed that MFAP2 was overexpressed in melanoma and promoted invasion and migration abilities of melanoma through regulating the EMT-related proteins and Wnt/beta-catenin pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Microfibrillar-associated protein 2 (MFAP2), also known as microfibril-associated glycoprotein 1 (MAGP1), is a component of extracellular elastic microfibrils, which interacts with fibrillin to influence the function of microfibers. 3 , 4 MFAP2 is the most widely distributed protein of MAGPs and a component protein of microfibrils in most vertebrates. A prominent feature of this protein is its ability to interact with TGF-β family growth factors, Notch and Notch ligands, and a variety of elastic fibrin.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we focused on MAGP1 since few studies had explored the relationship between MAGP1 and cancer, except the role in obesity, thermogenesis and homeostasis (12,27). We found that MAGP1 was overexpressed in most digestive system tumors like gastric cancer, cholangiocarcinoma, esophageal cancer, colon cancer, and rectal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Microfibril associated glycoprotein 1 (MAGP1), a small extracellular matrix molecule (21 kDa), is coded by the MFAP2 gene that is located on human chromosome 1p31 (11,12). Its Cterminal end includes a matrix-binding domain (MBD) which tethers it to the extracellular matrix (ECM) (11,12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation